2004
DOI: 10.1016/j.jtcvs.2004.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The salvage potential of coronary sinus interventions: meta-analysis and pathophysiologic consequences

Abstract: The use of intermittent coronary sinus occlusion and intermittent coronary sinus occlusion in combination with retroperfusion of arterial blood significantly decreases ischemic damage during coronary occlusions. Intermittent coronary sinus occlusion in combination with retroperfusion exhibits no significant profit in salvaging the ischemic myocardium in comparison with that provided by intermittent coronary sinus occlusion alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Syeda and colleagues reported no statistical difference in the salvage potential between these 2 methods in a meta-analysis of both methods, and showed that salvage was related to the developed pressure in the coronary sinus (CS). 3 Although both methods never reached widespread scientific acceptance, clinical data from a few human trials are available for both methods. 4,5 Retroperfusion was mainly studied in supporting coronary interventions and in cardiac surgery.…”
mentioning
confidence: 99%
“…Syeda and colleagues reported no statistical difference in the salvage potential between these 2 methods in a meta-analysis of both methods, and showed that salvage was related to the developed pressure in the coronary sinus (CS). 3 Although both methods never reached widespread scientific acceptance, clinical data from a few human trials are available for both methods. 4,5 Retroperfusion was mainly studied in supporting coronary interventions and in cardiac surgery.…”
mentioning
confidence: 99%
“…Using PICSO we were able to show in a canine model with 6 hours of permanent coronary artery occlusion a 50% infarct size reduction rated against the area at risk and an increase of the occluded coronary artery pressure. These data were corroborated worldwide and a Meta analysis of comparable data with different models of ischemia and reperfusion in different species of experimental animals showed a mean of 30% infarct size reduction [56,57].…”
Section: Werner Mohl MD Phd; Applied Coronary Hemodynamics and Workingmentioning
confidence: 61%
“…Syeda et al reported a significant reduction in infarct size of 29.3% in the pICSO group compared to the control group (p b 0.001; 95% confidence interval, −40.9 to −17.7), which correlated to the achieved (developed) coronary sinus pressure increase per minute (r = −0.92; p b 0.007) [52]. This dose-dependency has been recently confirmed by the Prepare RAMSES study, which showed a significant correlation (r = 0.70, p = 0.008) in reduction in infarct size and the cumulated coronary sinus pressure modulation over time [53].…”
Section: The Salvage Potential Of Picsomentioning
confidence: 97%
“…occlusion duration and elevation of the coronary venous systolic pressure per minute multiplied by the application times of ICSO) and infarct size [52]. The so-called "dose dependence" between optimized ICSO therapy and salvage has been documented in different species and different durations of ischemia [52].…”
Section: The Salvage Potential Of Picsomentioning
confidence: 99%